Stability and Shocks of EBITDA in Developed and Developing Countries: Evidence from Australia and Indonesia During the COVID-19 Pandemic - Sari, A. A. Pt. Agung Mirah Purnama (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study offers novelty through the use of EBITDA as the primary indicator in a comparative analysis of firms in developed and developing countries during the global crisis period (2019–2023). It highlights the role of government policy interventions in neutralizing the EBITDA gap and finds that firms in developing countries exhibit higher and more stable EBITDA compared to those in developed countries—a finding that challenges conventional views in the international economics literature. The purpose of this study is to analyze the differences in EBITDA between firms in developed and developing countries over the past five years using an unbalanced dataset. This study covers the period from 2019 to 2023 with a research population of 3,020 firms and 6,050 observations. The results show no significant differences in EBITDA between developed and developing countries in 2020, whereas differences are evident in 2019, 2021, 2022, and 2023. This condition may be partly explained by the COVID-19 pandemic, which led to government interventions in both countries. The analysis further shows that Indonesia has a higher average EBITDA ranking than Australia. A closer look at the descriptive statistics reveals that Australian firms are more volatile, while Indonesian firms appear far more stable.